Designing HOTS-Based Assessment Instrument for Hindu Religious Education in Junior High School - L. Eka M. Julianingsih P; Ni Luh Purnamasuari Prapnuwanti; Ketut Bali Sastrawan; Putu Wulandari Tristanda (Jurnal Edutech Undiksha, 2024)
The low level of critical and analytical thinking skills among students in understanding Hindu Religious Education materials indicates the need to develop an assessment instrument that fosters higher-order thinking skills (HOTS). This study aims to develop a HOTS-based assessment instrument for Hindu Religious Education in Grade IX of junior high school, with the goal of enhancing students' critical and analytical thinking abilities in comprehending the subject matter. The research employs the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subject comprises the developed instrument, with instrument feasibility as the research object. Data were collected using a questionnaire completed by expert lecturers and students of Hindu Religious Education. The results indicate that the developed instrument has a very high feasibility rating, based on trials conducted by lecturers with average percentages of 88.8% and 88.2%, respectively, falling into the "Very Feasible" category. The average score from the student response trial was 87.4%, placing the product within the "Very Good" category, which suggests its suitability for classroom use. It can be concluded that the developed assessment tool is not only valid and reliable but also effective in promoting critical thinking and cognitive engagement among students. By aligning the instrument with core competencies and HOTS indicators, this study contributes to ongoing efforts to improve educational practices, particularly in religious education.